2017
DOI: 10.1093/toxsci/kfx121
|View full text |Cite
|
Sign up to set email alerts
|

Editor’s Highlight: Mechanistic Toxicity Tests Based on an Adverse Outcome Pathway Network for Hepatic Steatosis

Abstract: Risk assessors use liver endpoints in rodent toxicology studies to assess the safety of chemical exposures. Yet, rodent endpoints may not accurately reflect human responses. For this reason and others, human-based invitro models are being developed and anchored to adverse outcome pathways to better predict adverse human health outcomes. Here, a networked adverse outcome pathway-guided selection of biology-based assays for lipid uptake, lipid efflux, fatty acid oxidation, and lipid accumulation were developed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 33 publications
2
47
0
Order By: Relevance
“…Predictions from the AOPBN for steatosis agreed with the results published in Angrish et al. () (Table ). It is important to recall that the AOPBN is completely independent of the data from Angrish et al.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Predictions from the AOPBN for steatosis agreed with the results published in Angrish et al. () (Table ). It is important to recall that the AOPBN is completely independent of the data from Angrish et al.…”
Section: Resultssupporting
confidence: 86%
“…Angrish et al. () confirmed that T0901317 and cyclosporin A both caused steatosis; the rest of the chemicals did not.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations